Perinatal results and first-year of life according to maternal skin color: A cohort study - de Oliveira, Juliana Eliseu [UNESP]; Ferrari, Anna Paula [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (My University, 2019)
Objective: To analyze the maternal characteristics and perinatal and the first year outcomes of life according to the self-reported color of the mothers. Method: Cohort study with mothers and their babies developed in a city in the interior of Sao Paulo. Followup occurred from June 2015 to February 2017. Data were collected at five moments: in the first month and at three, six, nine and 12 months of the child's life. Sociodemographic variables related to prenatal and delivery were included in the study. Among the perinatal outcomes, we analyzed the birth weight and the need for hospitalization in neonatal units; for the outcomes of the first year of life, the occurrence of respiratory infection and the breastfeeding duration were measured. Results: A total of 507 mothers participated in the study. Black/brown women presented an unfavorable socio-demographic situation when compared to white women. The only more favorable outcome among black/brown women was the breastfeeding duration. Conclusion: Despite the unfavorable sociodemographic situation considering the selected outcomes, black/brown women did not have worse results. The hypothesis that the quality of care may negate the negative effects of their sociodemographic conditions needs to be tested in future studies.
Resultados perinatais e do primeiro ano de vida segundo cor da pele materna: Estudo de coorte
Keywords: African continental ancestry group; Breast feeding; Maternal-child nursing; Perinatal care